Paper Actuators: Electrically Activated Paper Actuators (Adv. Funct. Mater. 15/2016). (April 2016) - Hamedi, Mahiar M.; Campbell, Victoria E.; Rothemund, Philipp; Güder, Firat; Christodouleas, Dionysios C.; Bloch, Jean‐Francis; Whitesides, George M.
Abstract : G. M. Whitesides and co‐workers describe, on page 2446, the design and fabrication of electrically controlled paper actuators made from paper, conducting polymer, and adhesive tape. The central element of the actuators is a porous conducting path providing electrothermal heating that changes the moisture content of the paper and causes actuation. These simple and inexpensive devices can achieve different types of motion such as bending and accordion‐type motion.